Non-Hodgkin lymphomas of oral cavity - Vicente-Barrero Mario; García-Castro Ines; Knežević Milan; Castellano-Reyes Jose Juan; García-Jimenez Francisco; Camacho-García María del Carmen; Baez-Acosta Beatriz; Lončarević Slobodan (Vojnosanitetski Pregled, 2002)
Non-Hodgkin lymphomas (NHL) often show up in an extranodal pattern, especially in the head and neck. Intraoral locations are much less frequent, particularly when they are single. This, in turn, can lead to a prolonged diagnosis and even to inadequate treatment. Different patients with initial extranodal location of NHL which were not previously diagnosed and in which it was manifested only intraoraly are presented in this paper. These cases are presented together with the additional examinations used for the early diagnosis and with the corresponding clinical pictures, as well as with the overview of other cases from the available literature.